Compulsive sexual behavior, sexual functioning problems, and their linkages to substance use among German medical students: exploring the role of sex and trauma exposure - Jepsen, Dennis; Luck, Tobias; Heckel, Christian; Niemann, Jana; Winter, Kristina; Watzke, Stefan (Frontiers in Psychology, 2024)
Sexual problems relevant to psychotherapy, such as compulsive sexual behavior (CSB) and sexual functioning problems (SFP) have been related to harmful substance use in several studies. Sub-stance use is high among medical students (MS) and is considered a maladaptive stress coping strategy and a risk factor for mental health problems. Sexual problems and substance use share trauma exposure and posttraumatic symptoms as risk factors for their development. This study aimed to explore the interaction effects between problematic sexual behaviors, substance use, and trauma in German MS. A cross-sectional study (n=359; 69% female, 29% male) was conducted using an online question-naire. MS at a German university were recruited via mail. CSB (CSBD-19), SFP (SBQ), harmful alcohol (AUDIT) and drug use (DAST), childhood trauma exposure (CTQ), and currently occurring posttraumatic symptoms (IES-R) were measured. Multivariate linear and ordinal regressions, as well as path analyses, were conducted to investigate associations between the study variables. CSB was found in 3% of all MS. Most reported SFP were decreased sexual desire and problems with achieving orgasm among females and premature ejaculation among males. Higher CSBD val-ues were predicted by male sex, higher AUDIT scores, and higher frequencies of hyperarousal (IES-R). Path analyses revealed associations between the severity of emotional/sexual abuse, intensity of posttraumatic symptoms, and CSBD and AUDIT scores. Among female MS, less severe emotional abuse and severe physical abuse in childhood predicted higher frequencies of problems with or-gasm. The frequency of SFP correlated with the consumption frequency of benzodiazepines among females, with cannabis and MDMA/ecstasy among male MS, and with cocaine/crack, speed, as well as with AUDIT among both sexes. No interaction effects were found for SFP, substance use, or trauma-related factors in path analyses. To some extent, there appears to be a relationship between substance use, childhood trauma expo-sure, and currently persisting posttraumatic symptoms with problematic sexual behaviors among MS. However, further research is required to explore these relationships more deeply and to identi-fy the respective pathways. Mental health support measures should include the factors of sexuality, substance use, and trauma and explore their relationship with workload, career-related anxieties, and other curriculum-related factors.